Evaluation of neurobehavioral and neurotoxicity effects of chronic embryonic heavy metal exposure on zebrafish (Danio rerio F. Hamilton, 1822) larvae - Abu Bakar, Noraini (2017)
Occurrence of industrialization without environmental care lead to heavy metals [Mercury chloride (HgCl2), Arsenic trioxide (As2O3)] contamination and caused adverse effects to human, especially vulnerable to developing fetus and children. Developmental exposures to heavy metals have been linked to impair motor and cognitive functions. However, the gap of knowledge to link between developmental exposure to heavy metal and neurodevelopmental disorders are still present. Thus, we used zebrafish to demonstrate the neurobehavioral and neurotoxic effects associated with the chronic embryonic exposure to low concentration of mercury and arsenic in a nanomolar to micromolar concentrations. The embryos were exposed to different range of HgCl2 (7.5-250 nM) and As2O3(20-50 μM) starting from 5 hpf until 72 hpf (hatching) in a semi-static condition. The mortality rate was increased in a dose dependent manner for both neurotoxicants. Exposure to 100 nM HgCl2and 30 μM As2O3decreased the number of tail coilings, heartbeat, and swimming activity. The adverse effects ofheavy metals on the development of anxiety-related behavior were assessed in 6 dpf larvae. No changes in thigmotaxis upon HgCl2and As2O3exposure were found. Yet, HgCl2exposures reduced swimming speed and elicit resting while As2O3exposure does not elicit any significant changes. Furthermore, aversive stimulation used to provoke anxiety responses also does not elicit any changes in thigmotaxis and avoidance response for both neurotoxicants. Overall, alteration in motor and anxiety responses were also linked with the increased apoptosis assessed at different time points. The peaks were shifted for both neurotoxicants whereby reaching an early peak at 24 hpf as compared to the control (72 hpf). Exposure to both neurotoxicants affects biochemical status (proteins, lipids, carbohydrates and nucleic acids) of the zebrafish larvae. These results showed that HgCl2and As2O3exert its toxic effects at cellular and biochemical level that leading to alteration at behavioral level